Bipolar disorder: burden of disease and related costs (Archives of Clinical Psychiatry, 2008)
BACKGROUND: Bipolar disorder (BD) is a recurrent, chronic and severe disease. Mental and physical comorbidities, risk of suicide, health services use and impairment of social and professional domains significantly worsen the burden and increase the costs of illness. OBJECTIVES: Review clinical aspects, burden of disease, and consequent financial outcomes of BD. METHODS: MEDLINE/PubMed database search using the terms bipolar disorder, epidemiology, burden of disease, comorbidity, cost of illness, outcomes e financial consequences, published in MEDLINE from 1980 to 2006. RESULTS: BD has a high rate of comorbidities, which worsen the prognosis and increase costs with health services. Subjects with BD have more cardiovascular risk factors than the general population, and therefore a higher risk of death by cardiovascular event. Delay of diagnosis and misdiagnosis increase the costs of illness. DISCUSSION: Comorbidities, risk of suicide, social and professional impairment and low adherence to treatment increase the cost of illness. The search of comorbidities may help clinicians to adjust treatment strategies, taking into account all associated risk factors and costs, which may be considered also by professionals involved in health care management, either private or public.